Meningkatkan Moderasi Beragama Melalui Dakwah Digital - Muhtadin, Agung Fathul; Syaputra, Akmal Hadi; Shafwan, Mochammad Rakandiya; Jenuri, Jenuri; Nurjaman, Asep Rudi (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
Increasing religious polarization in society, often fueled by extreme views and manipulation of proselytizing for specific interests, poses a risk to social stability. In Indonesia, this challenge is exacerbated by radicalism and resistance to religious moderation efforts. This study aims to explore how digital da'wah can be used to spread a more moderate and humanist narrative of religious moderation, as well as understand people's interpretations of moderate da'wah content. The method in this study is a quantitative with a descriptive approach. The results of this study obtained: 1) Digital da'wah has succeeded in reaching a wider audience, especially among today's young generation who actively use social media and the internet. Social media platforms and websites are effective channels for religious messengers to reach a wider audience. 2) The positive response to the effectiveness of digital da'wah shows that digitally distributed da'wah content has a positive impact on religious understanding and religious practice, which shows that digital da'wah is able to make an important contribution in strengthening the religious values of the community. 3) The use of information technology, especially social media and also the internet, is considered an effective means of spreading religious messages. The use of technology is an important factor in the success of digital da'wah to spread religious values to the wider community. Thus, digital da'wah has good effectiveness in increasing the dissemination of da'wah messages through social media to increase religious moderation in Indonesia.